Crystallization and optical properties of CCTO thin films under pressure influence - Sequinel, T. [UNESP]; Tebcherani, S. M.; Kubaski, E. T.; Oliveira, L. H.; Siu Li, M.; Varela, José Arana [UNESP] (My University, 2012)
CCTO thin films were deposited on Pt(111)/Ti/SiO 2/Si substrates using a chemical (polymeric precursor) and pressure method. The pressure effects on the CCTO thin films were evaluated by XRD, FEG-SEM and optical properties. Pressure films were found to be more homogeneous and dense than chemical deposition films. Pressure also leaded to an increase in the photoluminescence emission; it is suggested that the displacement of Ti in the titanate clusters, favors the charge transference from TiO 6 to [TiO 5V o z], TiO 5V o z] to [CaO 11V o z] and [TiO 5V o z] to [CuO 4] x. The low synthesis temperature used in the pressure method allows the deposition of films on less expensive substrates (i.e. glass, aluminum, polymer and others).
Keywords: CCTO; Pressure method; Thin films; Chemical deposition; Deposition of films; FEG-SEM; Photoluminescence emission; Polymeric precursors; Pressure films; Pt(111); Synthesis temperatures; TiO; XRD; Aluminum coatings; Exhibitions; Nanotechnology; Optical properties; Platinum; Polymer films; Polymers; Pressure effects; Vapor deposition; Nanocomposite films